Tissue Vitamin A Insufficiency Results in Adverse Ventricular Remodeling after Experimental Myocardial Infarction - Minicucci, Marcos Ferreira [UNESP]; Gaiolla, Paula Schmidt Azevedo [UNESP]; Oliveira, Silvio A.; Martinez, Paula F.; Chiuso-Minicucci, Fernanda [UNESP]; Polegato, Bertha Furlan [UNESP]; Justulin, Luis A. [UNESP]; Matsubara, Luiz Shiguero [UNESP]; Matsubara, Beatriz Bojikian [UNESP]; Paiva, Sergio Alberto Rupp de [UNESP]; Zornoff, Leonardo Antonio Mamede [UNESP] (Karger, 2010)
Background/Aims: The role of tissue vitamin-A insufficiency on post-infarction ventricular remodeling is unknown. We tested the hypothesis that cardiac vitamin A insufficiency on post-infarction is associated with adverse myocardial remodeling. Methods: After infarction, rats were allocated into two groups: C (controls, n=25); VA (dietary vitamin A restriction, n= 26). After 3 months, the animals were submitted to echocardiogram, morphometric and biochemical analysis. Results: Rats fed the vitamin-A-deficient diet had lower heart and liver retinol concentration and normal plasma retinol. There were no differences in infarct size between the groups. VA showed higher diastolic left ventricular area normalised by body weight (C= 1.81 +/- 0.4 cm2/kg, VA= 2.15 +/- 0.3 cm2/kg; p=0.03), left ventricular diameter (C= 9.4 +/- 1.4 mm, VA= 10.5 +/- 1.2 mm; p=0.04), but similar systolic ventricular fractional area change (C= 33.0 +/- 10.0 %, VA= 32.1 +/- 8.7 %; p=0.82). VA showed decreased isovolumetric relaxation time normalised by heart rate (C= 68.8 +/- 11.4 ms, VA= 56.3 +/- 16.8 ms; p=0.04). VA showed higher interstitial collagen fraction (C= 2.8 +/- 0.9 %, VA= 3.7 +/- 1.1 %; p=0.05). There were no differences in myosin heavy chain expression, metalloproteinase 2 and 9 activation, or IFN-gamma and TNF-alpha cardiac levels. Conclusion: Local tissue vitamin A insufficiency intensified ventricular remodeling after MI, worsening diastolic dysfunction. Copyright (C) 2010 S. Karger AG, Basel
Keywords: Ventricular function; Fibrosis; Ventricular dilatation